Replacing Truth with Social Hope and Progress with Redescription: Can the Pragmatist Philosophy of Richard Rorty Help Reinvigorate Planning?. (December 2022) - Lester, T. William
Through a review of Richard Rorty's philosophical work and critiques of original planning documents from the Urban Renewal era, this paper makes three points. First, a pragmatist epistemological approach offers a better foundation for planning than the current communicative paradigm. Second, updating planning's Enlightenment roots with Rorty's view of moral progress as a process of "redescription" can help reduce the anxiety planners feel in putting forward bold visions. Last, Rorty's concept of the liberal ironist provides an interesting model for planners that sees equal value in the contributions made by both the Jane Jacobs's and Robert Moses's of the field.